The dominance of directors, audit committee effectiveness and accounting conservatism: Malaysian evidence / Mohd Shatari Abd Ghafar - Abd Ghafar, Mohd Shatari (2012)
This study uses the alignment effect hypothesis from agency theory and the entrenchment hypothesis to examine the firms' financial reporting conservatism relative to the effectiveness of their audit committees and the dominance of directors. The study is also extended to determine the association of audit committee effectiveness and directors' dominance and their linkage to the firms' degree of accounting conservatism. The proxy for audit committee effectiveness in this study are audit committee independence, accounting financial expertise and diligence. Meanwhile, the proxies for directors' dominance are executive director's dominance, family director's dominance and audit committee shareholding. Using Khan and Watts's (2009) CSCORE measures of accounting conservatism, the CSCORE of 795 firms-year observation from Bursa Malaysia main board is calculated. The findings reveal that only professional accounting expertise and audit committee diligence are significant to explain the variations in the firms' financial reporting conservatism. The results also suggest that executive ownership and CEO duality are detrimental to firms' degree of accounting conservatism. Finally, it was found that the presence of professional financial accounting experts in the audit committees and audit committee diligence are able to strengthen the reporting conservatism in firms with high executive ownerships. The findings also suggest that an increase of professional accounting expertise in the audit committees and audit committee diligence are also able to moderate the negative association between Chief Executive Officer (CEO) duality and accounting conservatism. The findings from this thesis suggest the importance of having directors with professional accounting certification in the audit committees in order to provide efficient monitoring. The study also reveals that highly diligent audit committees play a huge part in encouraging conservative accounting. The findings also reveal some disturbing evidence. Contradictory to the general corporate governance principles, the association of audit committee independence is negative and insignificant. The implications from this findings, suggest that regulatory bodies should consider increasing the appointment of directors with professional accounting certifications in the audit committees. Besides that, it is also suggested that the committees should meet more frequently as by doing this they would have more time to monitor or review the financial reporting process. Furthermore, the roles and definition of "independence" of audit committees should be strengthened and revised.